DESAIN LEMBAR KERJA TERSTRUKTUR UNTUK MENGATASI KESULITAN MAHASISWA DALAM MEMAHAMI MATERI KONTINUITAS FUNGSI - Kus Andini Purbaningrum; Prahesti Tirta Safitri (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2022)
This study aims to design structured worksheets to overcome students' difficulties in understanding the continuity of functions in the differential calculus course. The research subjects were students of the mathematics education study program FKIP Muhammadiyah University of Tangerang (UMT). The Continuity of Functions material consists of several parts, namely the interval set of numbers, the limit of functions and graphs, and the continuity test of the function. This research is a formative evaluation type of development research. The stages used are self-evaluation, prototyping (expert reviews, one-to-one, and small group) to field tests. The results of the field test on the developed structured worksheets are in a very good category and are suitable for use as teaching materials to overcome student difficulties in understanding the material.